Symptoms of Music Performance Anxiety of Youth Orchestra Musicians - Techamanapong, Jirayu; Thuntawech, Saya (Journal of Education Studies, Chulalongkorn University, 2023)
Music performance anxiety (MPA) is a general phenomenon that happens to musicians. Orchestral musicians tend to experience higher levels of performance anxiety compared to individuals in other performing arts. The purpose of this research was to investigate the symptoms of MPA in youth orchestral musicians. The samples of this research were 72 current members of youth orchestras in Thailand. The research instrument used was the MPA symptoms questionnaire for youth orchestra including 67 items of the 6-level rating scale, developed from the previous MPA questionnaire, consisted of Music Performance Anxiety Inventory for Adolescents and Performance Anxiety Questionnaire, by the researcher. The data were analyzed using descriptive statistics. The results revealed that the average frequency of MPA in orchestral youth musicians is such that symptoms occur almost rarely or occasionally. Moreover, psychological symptoms tend to occur more frequently than physical symptoms. The average level of nervous symptom before performances is the highest. This study promotes music teachers’ ability to prepare young musicians to be aware of the MPA, then leading to the development of skills in managing MPA in future musical endeavors.